2006
DOI: 10.1007/s11745-006-5013-x
|View full text |Cite
|
Sign up to set email alerts
|

Acyl moieties modulate the effects of phospholipids on β‐carotene uptake by Caco‐2 cells

Abstract: The intestinal absorption of carotenoids is thought to be mediated by the carotenoid assembly in mixed micelles, followed by its transfer into the enterocytes and subsequent secretion to the lymph as chylomicron particles. In the present study we investigated the effects of phospholipids and lysophospholipids with diverse fatty acyl moieties on the uptake of beta-carotene solubilized in mixed micelles by Caco-2 cells. Compared with phospholipid-free mixed micelles (NoPL), those containing long-chain PC inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
3
29
1
Order By: Relevance
“…The promoting effect of lysophosphatidylcholine was correlated with the chain length of fatty acid moiety, with longer chain species showing a higher promoting effect. Unlike ordinary phosphatidylcholine with a long-chain fatty acid, medium-chain phosphatidylcholine, which is not present in biological tissues, showed a promoting effect equivalent to long-chain lysophosphatidylcholine (Yonekura et al 2006). Medium-chain phosphatidylcholine has hydrophile-lipophile balance equivalent to long-chain lysophosphatidylcholine, but at a higher level than longchain phosphatidylcholine.…”
Section: Intestinal Absorptionmentioning
confidence: 87%
“…The promoting effect of lysophosphatidylcholine was correlated with the chain length of fatty acid moiety, with longer chain species showing a higher promoting effect. Unlike ordinary phosphatidylcholine with a long-chain fatty acid, medium-chain phosphatidylcholine, which is not present in biological tissues, showed a promoting effect equivalent to long-chain lysophosphatidylcholine (Yonekura et al 2006). Medium-chain phosphatidylcholine has hydrophile-lipophile balance equivalent to long-chain lysophosphatidylcholine, but at a higher level than longchain phosphatidylcholine.…”
Section: Intestinal Absorptionmentioning
confidence: 87%
“…12,13) We found that the uptake of carotenoids by human intestinal Caco-2 cells was correlated with their lipophilicity, 14) confirming the simple diffusion mechanism. Furthermore, we have found that various PLs such as longchain phosphatidylcholines (PCs), [14][15][16] medium-chain PCs, 15) and lysophospholipids (lysoPLs) with different polar head groups 16) in mixed micelles markedly affect the uptake of micellar carotenoid by Caco-2 cells. Dietary and biliary lipid components would affect carotenoid uptake by intestinal cells.…”
mentioning
confidence: 99%
“…We succeeded in inducing different micelle sizes merely based on whether the 3-OH of LF 5 was protected or not by the levulinyl group. The interaction between these compounds fucoxanthin 3 , LevLF 4 , and LF 5 and a bile acid sodium taurocholate was confirmed by the measurements of full width at half maximum FWHM 32 in Table 1. FWHM values of the micelles entries 3 to 8 increased in comparison with the ethanol solutions of each compound 3, 4, and 5 , indicating these compounds formed a complex in the micellar inside.…”
Section: Measurements Of Micelles Sizementioning
confidence: 62%